KNOWLEDGE, ATTITUDE AND PRACTICES TOWARDS UTILIZATION OF EMERGENCY CONTRACEPTIVES AMONG FEMALE YOUTH AT NDEJJE HEALTH CENTRE IV, WAKISO DISTRICT. A DESCRIPTIVE CROSS-SECTION STUDY. - NABUNYA, GRACE; Kasujja , Hassan (Student’s Journal of Health Research Africa, 2023)
Background. The study aimed to find out the knowledge, attitude, and practices towards the utilization of emergency contraceptives among female youth. Methodology. The study used a cross-sectional study design with a simple random technique as a sampling technique on a sample of 50 respondents. Data was collected using questionnaires and semi-structured questionnaires; data was later analyzed manually systematically by compiling it in the form of percentage bar graphs, tables, and pie charts. Results. Findings from knowledge show that (88%) of the participants had ever heard about emergency contraceptives, (50%) obtained information about emergency contraceptives from the health facility, (82%) knew pills as the type of emergency contraceptive, (64%) knew after un- protected sex as the indicator of EC’s (84%) knew one dose as the recommended dose, (72%) knew within 72 hours as the recommended intervals and (44%) knew pharmacies as the places where they can obtain EC’s. Attitude towards utilization of EC’s was shown that (60%) of the respondents agreed that the effectiveness of emergency contraceptives in preventing unwanted pregnancies was high, (54%) agreed that emergency contraceptives should be availed to female youth, (74%) were willing to use emergency contraceptives if the need arises. The practices towards utilization of EC showed that (70%) were sexually active (82%) had ever used emergency contraceptives mostly once in a while as noted by (90%), (80%) had used pills as the emergency contraceptive method they had ever used and (39%) had never used emergency contraceptives because of sexual partner’s disapproval. Conclusion. Female youth possessed fairly suitable knowledge, attitudes, and practices toward emergency contraceptives though an infrequent percentage number of participants. Recommendations. Ndejje Health Centre IV administration should carry out extensive education and communication programs through community outreaches in areas where female youth are easily accessible to address many misconceptions and myths about emergency contraceptives.